Are antenatal steroids beneficial to severely growth restricted fetuses? - Mitsiakos, George; Kovacs, Lajos; Papageorgiou, Apostolos (The journal of maternal-fetal & neonatal medicine, 2013)
Antenatal steroids (AS) have been shown to enhance fetal maturation in preterms and to improve outcome. The aim of this study was to evaluate the efficacy of AS in premature severely intrauterine growth restricted infants. The electronic data of 149 inborn, single infants born 24 to 31 6/7 weeks of GA and with a BW ≤ 3rd percentile were reviewed. Infants with congenital anomalies and syndromes were excluded. We compared the outcome of those who received 2 doses of AS (group A, 87 infants) with those who did not receive AS (group B, 62 infants). Sixty-eight infants in group A and 53 in group B were discharged home alive. AS did not improve the neonatal outcome, with the exception of a better cord pH and 5-min Apgar and we did not observe a significant difference in the Griffith's test at 2 years of corrected age, although there was a trend to a higher incidence of severe global delay in the steroid group. In view of the potential cerebral and CVS risks associated with high circulating steroids, the indications for AS in such a population need to be re-evaluated.